1974
DOI: 10.1139/b74-209
|View full text |Cite
|
Sign up to set email alerts
|

The role of gibberellin and the hulls in the control of germination in Aegilops Kotschyi caryopses

Abstract: Large and small Aegilops Kotschyi caryopses have low α-amylase activity. After imbibition in water a marked increase takes place in α-amylase activity in the large, hulled and dehulled caryopses and only a slight increase in the small ones. Exogenously applied gibberellic acid (GA3) enhances α-amylase activity in both caryopses, and also improves germination of the small, hulled caryopses.Removing parts of the hull from different sites on the palea or lemma of the small caryopses improves germination. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…A delayed germination in the smaller seeds of several Aegilops has also been observed in natural conditions (i.e. with seeds enclosed in the dispersal unit) and explained by the influences of both maternal and sibling factors, through the presence of an inhibitor in the glumes, internal levels of gibbellerins or competition for essential metabolites among sibling seeds (Lavie et al ., 1974; Wurzburger and Leshem, 1967; Wurzburger and Leshem, 1969; Wurzburger and Koller, 1973; Dyer, 2004). However, the implications of such constrains on the emergence phenology in nature were not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…A delayed germination in the smaller seeds of several Aegilops has also been observed in natural conditions (i.e. with seeds enclosed in the dispersal unit) and explained by the influences of both maternal and sibling factors, through the presence of an inhibitor in the glumes, internal levels of gibbellerins or competition for essential metabolites among sibling seeds (Lavie et al ., 1974; Wurzburger and Leshem, 1967; Wurzburger and Leshem, 1969; Wurzburger and Koller, 1973; Dyer, 2004). However, the implications of such constrains on the emergence phenology in nature were not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this response may be a combination of both physical and embryo dormancy. Wurzburger (1974) stated that the glumes in Aegilops might act not only as a physical barrier to the entry of oxygen but also as a biochemical barrier to germination.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of 20 mM KNO3 to the pH 3 buffer plus GA3 did not further increase germination (Table 1). Frankland and Wareing (1966) and Wurzburger et al (1974) reported enhanced germination response to GA3 after disruptions of structures enclosing the seeds. Of the several methods available, scarification in concentrated H2SO4 (density 1.83) seemed most convenient for use on B. vulgaris.…”
Section: Data Presented Inmentioning
confidence: 99%